Development of a 3-cylinder Gasoline Engine Concept - Jonsson, Björn; Lundahl, Daniel (My University, 2013)
The master thesis is performed on request by Volvo Car Corporation (VCC) with focus on evaluating if a 3-cylinder engine could replace a mid- to high performance 4-cylinder engine. The developed 3-cylinder engine concept is compared to a benchmark 4-cylinder engine provided by VCC with respect to steady state performance and fuel consumption as well as transient response (Time-To-Torque). The 3-cylinder engine model is developed, tested and evaluated with GT-Power but it has not been fully validated with test-rig data. The engine concept is developed from a 2.0 litre 4-cylinder SI engine where one cylinder has been removed to create a 1.5 litre 3-cylinder SI engine, which is boosted with a single-scroll turbocharger. Several technologies are investigated based on a literature study with the aim of reducing the fuel consumption and utilize synergistic effects, i.e. the investigated technologies are meant to have the possibility of being combined. Technologies that are evaluated are different turbocharger set-ups, Fully Variable Valve Train (FVVT), Two-Stage Valve Lift (TSVL), Dual Individual Cam Phasing (DICP), Integrated Exhaust Manifold (IEM) and Cylinder Deactivation. A comparison of the 4-cylinder engine with the 3-cylinder concept engine at different part load points reduced the fuel consumption of the 3-cylinder engine by 6-14%. The 3-cylinder engine was evaluated at 3bar IMEP at 2000rpm with TSVL and FVVT for early intake valve closing. The reduction in fuel consumption was 4.6% and 6% respectively. At the same part load point, cylinder deactivation on the 3-cylinder engine reduced the fuel consumption by 17.7% and 23.5% compared to the 3- and 4-cylinder engine respectively, only equipped with DICP. Two different turbines for the single-scroll turbocharger have been evaluated which both fulfils the performance targets. The smaller turbine showed high levels of backpressure, and therefore an alternative with limited backpressure was presented. The turbine with limited backpressure resulted in 1.6% lower peak power compared to the benchmark 4-cylinder engine and the 50mm turbine was able to produce 3.1% higher peak power. Both turbines reached the torque knee 300rpm later compared to the benchmark engine. The 45mm turbine has the best transient response and matches the benchmark engine if the engine speed is increased by 300rpm. An Integrated Exhaust Manifold (IEM), which particularly suits a 3-cylinder engine, has been evaluated on the concept engine. The IEM shows improvements in decreasing the exhaust gas temperature which reduces the need of mixture enrichment to decrease the temperatures at full load.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport